Footprint of the COVID-19 Pandemic in India: A Study of Immune Landscape and Other Factors Shielding Mortality - Noura Al-Dayan; Divya Venugopal; Sugapriya Dhanasekaran (Analytical Cellular Pathology)
The impact of the SARS-CoV-2 pandemic has significantly affected global health and created a world crisis. The exponentially increasing numbers of infection and mortality have made preventive measures challenging. India being a highly populated nation has so far effectively counteracted the pandemic outbreak with a significantly lower rate of mortality despite the high infection rates. The genetic architecture of the immune response genes in the Indian population, BCG vaccination, the predominantly young age group of people, and their traditional food habits might contribute to the lower rate of mortality. Human leukocyte antigens (HLA) play a vital role in triggering T cells, and natural killer (NK) cells can immediately react to eliminate infected cells. Activation of virus-specific CD4+ T cells and CD8+ cytotoxic T cells selectively targets the infected cells and strengthens the immunoregulatory system. The checkpoint for NK cell function is the engagement of killer Ig-like receptors (KIR) molecules with their respective HLA ligands overexpressed or expressed on the compromised virus-infected cells which have shown polymorphism among different ethnic groups. Here, we explore if certain KIR-HLA motifs grant Indians a survival advantage in terms of the low rate of mortality. Additionally, enhanced immunity through BCG vaccination may favor fruitful eradication of SARS-CoV-2 and provide the way out as in therapeutic intervention and vaccination strategies.